Co-occurrence of pectenotoxins and Dinophysis miles in an Indonesian semi-enclosed bay. (December 2022) - Likumahua, Sem; de Boer, M. Karin; Krock, Bernd; Tatipatta, Willem M.; Abdul, Malik S.; Buma, Anita G.J.
Abstract: The study aims to unravel the variability of Dinophysis spp. and their alleged toxins in conjunction with environmental drivers in Ambon Bay. Phytoplankton samples, lipophilic toxins and physiochemical water properties were analysed during a 1.5-year period. Three Dinophysis species ( D. miles, D. caudata, and D. acuminata ) were found in plankton samples, of which D. miles was the most abundant and persistently occurring species. Pectenotoxin-2 (PTX2) and its secoacid (PTX2sa) were detected throughout, and PTX2sa levels strongly correlated with D. miles cell abundance. The toxin showed a positive correlation with temperature, which may suggest that D. miles cells contain rather constant PTX2sa during warmer months. Dissolved nitrate concentrations were found to play a major role in regulating cell abundances and toxin levels. This study adds adequate information regarding marine biotoxins and potentially toxic species for future Harmful Algal Bloom management in Ambon and Indonesia at large. Highlights: Dinophysis miles is the most abundant species and found persistently in Ambon Bay. Pectenotoxin-2 and its secoacid are detected and have strong correlations with Dinophysis miles cells. The pectenotoxin-2 secoacid is likely produced during the dry season with high temperature levels. Nitrate is the main factor controlling both Dinophysis miles cells and the toxins.